Root anatomy of mandibular second premolars in french subpopulation: A retrospective observational case series - Naji Kharouf; Youssef Haikel; Davide Mancino (Wolters Kluwer Medknow Publications, 2019)
Aims: The purpose of this in vivo study is to illustrate endodontic anatomical variants in French subpopulations of human mandibular second premolars to show if the literature matches our findings. Setting and Design: This was an observational retrospective study. Subjects and Methods: This study was performed from September 2016 to September 2017. It was conducted on 56 successive cases of root canal therapies on the mandibular second premolars. All procedures were done in conformity with current state-of-the-art practices in endodontics. These included rigorous clinical and radiographic preaccess analysis, appropriate tooth restoration to insure watertight rubber dam installation, surgical microscopic manipulations for precision, systematic use of ultrasonic endodontic tips to manage cavity access preparation, and step-down technique to shape the root canal systems. Statistical Analysis Used: Fifty-six mandibular second premolars were treated: 76.8% had one canal, and 23.2% had two or more canals. Conclusions: The incidence of two or more canals on mandibular second premolars could be underestimated as our results show. To prevent any missing canals, clinicians must have a perfect knowledge of anatomic variants of the root canal system. Moreover, the systematic use of a surgical microscope, ultrasonic endodontic tips, and a modern step-down technique should facilitate and standardize access cavity preparation, canal localization, and instrumentation.